2022
DOI: 10.1002/cac2.12394
|View full text |Cite
|
Sign up to set email alerts
|

Targeting immune checkpoints: how to use natural killer cells for fighting against solid tumors

Abstract: Natural killer (NK) cells are unique innate immune cells that mediate antiviral and anti-tumor responses. Thus, they might hold great potential for cancer immunotherapy. NK cell adoptive immunotherapy in humans has shown

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 328 publications
0
3
0
Order By: Relevance
“…They are called the “first line of defense” because, different from T lymphocytes, they do not express antigen-specific T cell receptors but act against mutated cells without prior sensitization or clonal expansion [ 95 ]. NK cell adoptive immunotherapy failed to show efficacy in the treatment of solid tumors, partly due to the immunosuppressive TME and lack of NK cell specificity to the tumor [ 96 ].…”
Section: Aptamer-based Immune Strategies For Tnbc Treatmentmentioning
confidence: 99%
“…They are called the “first line of defense” because, different from T lymphocytes, they do not express antigen-specific T cell receptors but act against mutated cells without prior sensitization or clonal expansion [ 95 ]. NK cell adoptive immunotherapy failed to show efficacy in the treatment of solid tumors, partly due to the immunosuppressive TME and lack of NK cell specificity to the tumor [ 96 ].…”
Section: Aptamer-based Immune Strategies For Tnbc Treatmentmentioning
confidence: 99%
“…Researchers have stated that blocking immune checkpoints not only rescues NK cells from exhaustion but also increases their robust antitumor functions [36]. Deleting TIPE2 and CISH, two intracellular checkpoint genes, had a synergistic effect in preventing NK cell exhaustion as well as improving antitumor activity [36]. Previous research studies have shown that disrupting the PD-1 pathway induces the production of cytokines, which may in turn increase tumor infiltration [37].…”
Section: Overcoming the Viability Barriers Of Nk Cell-based Immunothe...mentioning
confidence: 99%
“…Lately, the status quo of reversing NK cell exhaustion has been targeting immune checkpoints. Researchers have stated that blocking immune checkpoints not only rescues NK cells from exhaustion but also increases their robust antitumor functions [36]. Deleting TIPE2 and CISH, two intracellular checkpoint genes, had a synergistic effect in preventing NK cell exhaustion as well as improving antitumor activity [36].…”
Section: Overcoming the Viability Barriers Of Nk Cell-based Immunothe...mentioning
confidence: 99%
“…These checkpoints play a key role in balancing the activity of the immune system, enabling it to respond to pathogens and cancer cells while avoiding damage to healthy tissues. However, cancer cells can sometimes use these checkpoints to avoid being attacked by the immune system [35][36][37]. They express certain proteins that interact with checkpoint receptors on immune cells, effectively suppressing the immune response against cancer cells.…”
Section: Introductionmentioning
confidence: 99%